PENGARUH VARIASI SUHU PENGERING TERHADAP MUTU DENDENG IKAN LELE DUMBO (Clarias gariepinus) - Muhammad Ikhsan; Muhsin Muhsin; Patang Patang (Universitas Negeri Makassar, 2016)
The aims of this research is to know the quality of chemical and hedonik Catfish jerky. This research used a completely randomized design (CRD) with 3 treatment drying temperature of 60oC, 65oC and 70oC. The observed parameters is moisture, protein, fat content and quality hedonik catfish jerky. The results showed a drying temperature of 65oC is the best treatment with moisture content 25,02%, protein 16,04%, fat content 39,54%, hedonik color 3.88, hedonik texture 3.77, hedonik aroma 3.75 and hedonik sense of 3.80